Seizures and Phytotherapy: The Most Important Medicinal Plants Used for Seizures in Children and Adults in Iranian Ethnobotanical Documents - Halleh Mirbehresi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Due to the relatively high prevalence of seizures (8%), the cases of prescribing these drugs are very high and usually have many side effects, so in this review study, the use of medicinal plants in different regions of Iran in ethnobotanical documents was extracted and reported. In this study, for this purpose, keywords such as convulsion (seizure), medicinal plants, ethnobotany, identification of medicinal plants, region and Iran were performed. Databases such as ISI Web of Science, PubMed, Scopus, ISC, Magiran and Google Scholar were used to review articles and resources. Based on the results, Anthemis nobilis L., Leonurus cardiac L., Lotus corniculatus L., Hyoscyamus niger L., Salvia spp., Grammosciadium platycarpum Boiss. & Hausskn., Nigella sativa L., Anethum graveolens L., Papaver fugax Poir., Lotus corniculatus L., Verbascum thapsus L., Ferula assa-foetida L., Ferula gumosa Boiss., Heracleum persicum Desf.ex Fischer., Angelica archangelica L., Vicia faba L., Verbascum pseudonobile Stoj & Stef., Melissa officinalis L., Teucrium polium L., Datura stramonium L., Hymenocrater spp. and Melissa officinalis L., are medicinal plants that are used in different parts of Iran to treat seizures. The data collected in this study were analyzed using Microsoft Excel program. According to the results, the plants of this study belong to 11 plant families. The aerial part with 32% is the most plant part used for seizures. Also, most of the medicinal plants used to treat seizures were related to the northern region of Khuzestan. Ethnobotanical knowledge can provide pure ideas for modern pharmacological knowledge and lead to the production of effective natural anticonvulsant drugs.